Le Corbusier’s Urban Planning as a Cultural Legacy. An Approach to the Case of Chandigarh - Juan-Andrés Rodríguez-Lora; Ana Rosado; Daniel Navas-Carrillo (Designs, 2021)
The uniqueness and importance of Le Corbusier’s work were ratified by the recognition and inclusion of 17 of his projects as heritage legacy on UNESCO’s (The United Nations Educational, Scientific and Cultural Organization) World Heritage List in 2016. Despite the disciplinary diversity of his entire career, it is his architectural work that enjoys the greatest levels of dissemination and recognition. Consequently, it is assumed that Le Corbusier’s architectural work is more protected than its urban plans. This article aims to advance the recognition of the latter. To this end, it proposes a cartographic and documentary review of his projects, a specialized bibliographic review, as well as a review of national and international databases on his built work. Of 88 built works, at least 51 have some kind of heritage protection. In any case, less attention is paid to the urban dimension of his work. The city of Chandigarh presents a series of particularities, apart from being the only Corbusierian city built, which could raise the need for its safeguarding and recognition as a cultural legacy. 20th-century urban planning, and Chandigarh in particular, require the application of criteria complementary to those usually applied in heritage protection in object-based approaches.